Marchands de Miracles . Merchants of Miracles - Remiche, Gilles (Les Films de la Passerelle, 2006)
Verzio FF submission In a country torn apart by war, poverty and disease, it seems that everyone is on the lookout for a miracle. Luckily, in the Democratic Republic of Congo miracles are part of everyday life thanks to a few charismatic pastors who preach the word of the Lord and work wonders in their "churches of awakening." Reminiscent of the mega-churches in the Unites States, these gigantic congregations boast a mix of Christian values and traditional African beliefs and at the center of each devoted group of followers there stands a "prophet" who claims to be able to cure AIDS, provide material wealth and resurrect the dead. Gilles Remiche travels to Kinshasa where prophets and pastors can be found roaming the streets, holding court in auditoriums and on TV programs, to speak to the men behind this spiritual movement as well as the people who have chosen to follow the self-proclaims healers. Hovering between cynicism, megalomania and surrealism, these prophets feed off the desperation of followers whose generous donations feed their lavish lifestyles.